Genetic diversity and structure of red handed howler monkeys assessed by mitochondrial and genotyping by sequencing analyses - Jacqueline Vieira Gardellin; Carla C. Gestich; Pedro M. Galetti; Luana Portela; Victor Yunes Guimarães; Fabiano Rodrigues de Melo; Amy Goldberg; Patrícia Domingues de Freitas (Scientific Reports)
Abstract The red-handed howler monkey, Alouatta belzebul, has an uncertain taxonomy complex that includes A. belzebul, A. discolor and A. ululata. These primates are endemic to Brazil and are classified as vulnerable or endangered by the IUCN Red List due to population declines over the past 40 years. Damming by hydroelectric power plants is the greatest threat to the taxa. The recent implantation of the fourth largest dam worldwide (Belo Monte Hydroelectric Dam, UHBM) threatens their populations, because its flooding zone covers areas where A. belzebul and A. discolor may co-occur. Determining species classification is crucial for conservation efforts. Here, we characterized the genetic diversity and structure of howler monkeys rescued before the flooding. We performed Genotyping by Sequencing (GBS) analyses and constructed a mitochondrial-based phylogenetic tree and a haplotype network in specimens identified as A. belzebul, based on their coat color, from both banks of the Xingu River and three islands. The study revealed the occurrence of both taxa, indicating high genetic diversity. These findings are valuable for understanding group diversity, providing reference data for monitoring populations in the region and implementing conservation actions, as well as serving as a model for similar studies of other taxa.